The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1159/000331138
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors versus Histamine-2-Receptor Antagonists for the Management of Iatrogenic Gastric Ulcer after Endoscopic Mucosal Resection or Endoscopic Submucosal Dissection: A Meta-Analysis of Randomized Trials

Abstract: Background/Aims: Both proton pump inhibitor (PPI) and histamine-2-receptor antagonist (H2RA) are considered to be effective for the treatment of iatrogenic gastric ulcer after endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD). We aimed to systematically evaluate the evidence comparing PPI and H2RA for iatrogenic ulcer. Methods: Data from PubMed, Cochrane Library and Google Scholar were searched to identify eligible randomized trials. Outcome measures were delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 52 publications
(52 reference statements)
0
65
1
Order By: Relevance
“…10,11 In this case, the patient was diagnosed with MDS, and the patient's platelet count was 21,000/mm 3 on the day of the ESD, but the transfusion of platelet concentrates enabled us to perform the procedure without bleeding. PPI administration also might have contributed to the prevention of post-ESD bleeding.…”
Section: Discussionmentioning
confidence: 93%
“…10,11 In this case, the patient was diagnosed with MDS, and the patient's platelet count was 21,000/mm 3 on the day of the ESD, but the transfusion of platelet concentrates enabled us to perform the procedure without bleeding. PPI administration also might have contributed to the prevention of post-ESD bleeding.…”
Section: Discussionmentioning
confidence: 93%
“…These discrepancies may be attributed to the type and dosage of drug used, follow-up duration, or sample size. Recently, a metaanalysis revealed that PPIs are superior to H 2 RAs for the prevention of delayed bleeding without significant changes in symptom resolution or ulcer healing after EMR or ESD [23]. PPIs have been used widely because they are more effective at elevating the intragastric pH than H 2 RAs.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, an 8-week treatment was found to be more effective than 4-week treatment. However, ulcer healing rate at 4 or 8 weeks of treatment seem to be equivalent (103). Recently, several randomized controlled trials compared the combination of PPI and mucosal protective agents (being the most promising rebamipide) with PPI monotherapy in the healing of iatrogenic ulcer after ESD.…”
Section: Pharmacological Treatment Only Two Randomizedmentioning
confidence: 99%